Aesthetics of Images and Symbols - Dilbar Solihovna (International Journal on Integrated Education, 2021)
This article examines the aesthetic, religious, philosophical and spiritual aspects of the image and symbol, the scientific and social significance of their correct analysis and interpretation, as well as some of their specific aspects, such as the polysemy of meaning.